EFEKTIVITAS MULTIMEDIA INTERAKTIF BERBASIS DISCOVERY LEARNING BERBANTUAN GOOGLE SITES PADA MATERI GERAK PARABOLA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Rizkina Putri Akmalia; Dea Stivani Suherman; Fatni Mufit; Emiliannur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of Discovery Learning-based interactive multimedia assisted by Google Sites on students’ critical thinking skills in projectile motion material. This research employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group design. The research sample consisted of two classes selected using a simple random sampling technique, namely the control class and the experimental class. The instrument used was an essay test based on six indicators of critical thinking according to Facione: interpretation, analysis, evaluation, inference, explanation, and self-regulation. The results showed a difference in critical thinking skills between the two classes. Hypothesis testing produced a significance value of 0.000 (< 0.05), with the average posttest score of the experimental class (78.13) being higher than that of the control class (62.11). The N-Gain results indicated that the improvement in the experimental class was in the high category, while the control class was in the moderate category. In addition, the effect size analysis showed a Cohen’s d value of 1.10, which falls into the large category. Based on these findings, it can be concluded that Discovery Learning-based interactive multimedia assisted by Google Sites is effective in improving students’ critical thinking skills on projectile motion material compared to conventional learning.